“Underdevelopment”, “Backwardness” and “ Development”: The ‘History Construction’ of the Left in the case of Ismail Cem in 1960s Turkey - Sedat Gencer (İnsan & Toplum)
İsmail Cem (1940-2007) is one of the prominent names of Turkish intellectual and political life. Although his political career drew great attention, evaluation of his intellectual out- put has always been in the shadow of this political interest. Cem contributed to the discussions lead by the left wing in the 60s on the developement of Turkey through his work, “The History of Backwardness in Turkey”. During that period, İsmail Cem produced a Marxist macro analysis that was mentioned along with other macro analyses by leading intellectuals such as Doğan Avcıoğlu, İdris Küçükömer, Behice Boran, and Niyazi Berkes. Discussions of this era were conducted within the framework of concepts such as Underdevelopment, Backwardness, Feudality and the Asiatic Mode of Production. In this era, left wing intellectuals, and political parties and movements came up with solutions to the problems that Turkey faced with their perspectives based on analysis of the Ottoman past. The comments based on the distinctiveness of the structure of Ottoman Society and its similarity to the West were shaped by the answers to the question, “why could not the Ottoman Empire adopt Capitalism?” The main purpose of this article is to determine İsmail Cem’s intellectual position in the 1960s. In this regard, what his ideas meant for the left wing will be researched and the question of his intellectual identity’s originality will be discussed by study- ing his intellectual references in conjunction with the conditions of that era.